Installation for maintaining the operating temperature of electrolytes when restoring machine parts with electroplated coatings - A. N. Kotomchin; A. F. Sinelnikov (Вестник СибАДИ)
Introduction. The use of electroplating in the production and restoration of machine parts is important for increasing reliability and reducing costs in the operation of cars. At the same time, strengthening and restoring parts with chrome, iron and alloys based on them leads to additional costs, due to the specifics of technologies and the need to maintain certain operating temperatures of electrolytes to obtain high-quality and high-performance precipitation. Since existing devices for maintaining the temperature of the electrolyte have a complex design and require additional energy costs, we are constantly searching for ways and designs that will simplify the design, increase its reliability and reduce energy costs.Materials and methods. The current method for maintaining the temperature of electrolytes of current bath is taken as a prototype for the research. An improved plant was designed and tested in real conditions for the production of chrome, iron precipitation and alloys based on them.Results. The developed installation makes it possible to reduce energy consumption and improve the quality of electrolytic coatings. The developed installation allowed maintaining the temperature in the required range, both at low temperatures of 20÷35oC and at high temperatures of 40÷60oC.Discussion and conclusion. As a result of the analysis of the existing methods for maintaining the temperature of the electrolyte, their shortcomings are identified and a new method is proposed that will allow controlling and maintaining the necessary operating temperature of the electrolyte in the required operating range without significant fluctuations. The developed installation can be put into production, which will allow industrial use of complex temperature-sensitive chrome plating technologies, while obtaining high-quality electroplating coatings.